Stock Prices Affected by Good Corporate Governance and Financial Performance - Fayanni, Yenni; Soetedjo, Soegeng (Opción)
In this study, the authors propose to evaluate the application of Good Corporate Governance and Financial Performance to the stock prices of manufacturing companies listed on the Indonesia Stock Exchange. The research method used is descriptive method with a quantitative approach. In this statement, the population used in this study is the financial statements of manufacturing companies listed on the Indonesian stock exchange from 2016 to 2018, the technique of determining the sampling uses Purposive Sampling. This research data uses secondary data, financial statements of manufacturing companies listed on the Indonesia stock exchange from 2016 to 2018. All data sources were obtained from the website of the Indonesia Stock Exchange at https://www.idx.co. ID, company website as well as Google search. Our analysis reveals that Independent Commissioners and Managerial Ownership, PBV and NPM affect stock prices, while for Institutional Ownership does not affect stock prices. The value of implementing Good Corporate Governance and Financial Performance on the price of manufacturing companies listed on the Indonesia Stock Exchange is 64.5%, while 35.4% is explained by other factors which are not included in this study.